Isolated and combined linkage of insufficient physical activity and excessive sitting time on college students’ negatively self-related health - Jean Carlos Parmigiani De Marco; Andreia Pelegrini; Danielle Ledur Antes (Pensar en Movimiento)
The objective of this study was to analyze the isolated and combined linkage of insufficient physical activity and excessive sitting time on negatively self-rated health in university students. This is a cross-sectional study conducted with 418 students from a community university in western Santa Catarina, Brazil. Self-rated health was the dependent variable. Self-reported information on moderate to vigorous physical activity and sitting time was collected through a questionnaire. University students were classified as insufficiently active or with excessive sitting time if they did not meet the recommended guidelines. For the analysis, models were developed that considered physical activity and sitting time in isolation and in combination, using those who did meet the guidelines as a reference. The data was analyzed using Poisson regression, with adjustment for sociodemographic variables and characteristics related to the participants' degree. Results show that most of the participants were women (73.4%) and the average age was 22.9 years (SD = 5.3). Three out of every 10 university students had a negatively self-rated health. In addition, individually, insufficiently active university students and those with excessive sitting time were 1.73 (95% CI = 1.25-2.40) and 1.40 (95% CI = 1.05-1.87) times more likely to report a negatively self-rated health. In the combined analysis, when presenting both risk factors simultaneously, the probability of presenting negatively self-rated health was 2.76 (95% CI = 1.62 – 4.71). College students with insufficient physical activity and excessive sitting time are at a higher risk of negatively self-rated health, particularly when both behaviors are present simultaneously.